MODELS AND ALGORITHMS FOR COMPUTER-AIDED DESIGN OF TECHNOLOGICAL PROCESS OF CASTINGS PRODUCTION, DIRECTED FOR SUPERCOMPUTER SKIF - A. N. Chichko; T. V. Matjushinets; L. V. Markov; S. G. Lihousov; V. F. Sobolev; O. I. Chichko (Литьë и металлургия)
The schema of development and technological process of castings production under supercomputer SKIF,  which al lows to decrease the periods of gating systems projecting, is  offered.  The model for appraisal of the variants of the castings production technology, which allows to range the modeled  technological processes and to choose the optimal regimes and gating system, is developed.